Finger hold relaxation intervention on reducing pain intensity in postoperative craniotomy patients in the Dahlia Room of Dr. Doris Sylvanus Hospital in 2025 - Ristiana, Ayu; Sylvia, Ester Inung; Supriandi; Datak, Gad (Institute Of Computer Science (IOCS), 2025)
Postoperative craniotomy pain is a common issue experienced by approximately 90% of patients within the first 48 hours after surgery. Effective pain management is crucial to prevent the progression of acute pain into chronic pain, which can hinder the patient’s recovery. This study aims to evaluate the effectiveness of the finger grasp relaxation technique as a nonpharmacological intervention in post-craniotomy care. A descriptive design with a case study approach was used, involving two respondents who had undergone craniotomy at RSUD dr. Doris Sylvanus Palangka Raya. Data were collected through semi-structured interviews and direct observation. Data validity was ensured through source and method triangulation, and reliability was maintained by repeated measurement from two observers. Pain intensity was assessed using the Numerical Rating Scale (NRS) before and after the intervention. The finger grasp relaxation technique was applied for 15 minutes per session, once daily for three consecutive days. This technique is distinctive in combining gentle finger pressure with regulated breathing to stimulate reflex points believed to influence the central nervous system. The results indicated a decrease in pain intensity from a score of 5 to 2 in the first respondent, and from 6 to 2 in the second respondent, accompanied by a reduction in pain duration. Despite limitations such as a small sample size, the finger grasp relaxation technique has proven to be an effective, simple, and safe nonpharmacological therapy, with potential for application in nursing practice for postoperative pain management in craniotomy patients.